Screening of effective biosurfactant-producing bacteria from plant rhizosphere and oil-polluted soils - Gordeev Alexander; Biktasheva Liliya; Galitskaya Polina (BIO Web of Conferences)
Identification and characterization of effective biosurfactant-producing strains is critical for the successful implementation of a wide range of biotechnological processes. This study used a comprehensive screening approach of potential biosurfactant producing bacteria isolated from plant rhizosphere and oil polluted soils. A total of 63 isolates were obtained and their ability to produce biosurfactants was assessed based on the emulsification index (E24) and surface tension measurements using cell-free culture supernatants. The results revealed significant differences in the potential of isolates to produce surfactants, with E24 values ranging from 5% to 81% and surface tension values ranging from 27.1 to 68.1 mN m-1. The most promising biosurfactant-producing strains were able to reduce the surface tension of the culture medium to values below 30 mN m-1 and demonstrated high emulsification indices (>40%), indicating their ability to produce biosurfactants in concentrations sufficient to exhibit high surfactant and emulsifying properties. Using the Sanger sequencing method, the three strains with the highest biosurfactant producing potential were identified as B. mojavensis, P. fluorescens, P. putida.